2015
DOI: 10.3109/03009742.2015.1028997
|View full text |Cite
|
Sign up to set email alerts
|

Adherence to cardiovascular prevention strategies in patients with rheumatoid arthritis

Abstract: RA patients tend to underestimate their CVD risk. The self-reported adherence of RA patients to CVD risk management was high concerning pharmaceutical interventions and moderate in the case of lifestyle interventions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
15
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(16 citation statements)
references
References 25 publications
1
15
0
Order By: Relevance
“…Therefore, they indirectly support the need to improve the management of CV risk, which is still found to be inadequate. 24 Our study has some strengths and limitations. It is the first study on mortality in Italian RA patients, the vital status of whom was known in 93% of patients at the end of follow-up.…”
Section: Discussionmentioning
confidence: 98%
“…Therefore, they indirectly support the need to improve the management of CV risk, which is still found to be inadequate. 24 Our study has some strengths and limitations. It is the first study on mortality in Italian RA patients, the vital status of whom was known in 93% of patients at the end of follow-up.…”
Section: Discussionmentioning
confidence: 98%
“…We hypothesized that the detected differences might be ascribed either to the careful follow-up that RA patients undergo in tertiary centers, which may decrease mortality by cancer and infections, or to epidemiological differences among RA cohorts from different countries or both these aspects. 25 …”
Section: Discussionmentioning
confidence: 99%
“…9,69 A 2015 cross-sectional study involving 111 patients with rheumatoid arthritis found that, although 53% of these patients were estimated to be at high risk for CVD (defined as a 10-year risk of CVD events of 20% or more), only 3% thought they were at increased cardiovascular risk. 69 This underrecognition of risk may contribute to lower patient adherence to provider recommendations about CVD risk reduction strategies. 69 Lack of awareness among health care providers may also be a factor.…”
Section: Underrecognition Of Cardiovascular Disease and Undertreatmenmentioning
confidence: 99%
“…69 This underrecognition of risk may contribute to lower patient adherence to provider recommendations about CVD risk reduction strategies. 69 Lack of awareness among health care providers may also be a factor. In 2016, a qualitative study involving physicians who provide care to patients with rheumatoid arthritis found that about half of the primary care providers who were interviewed were unaware of the increased CVD risk in these patients.…”
Section: Underrecognition Of Cardiovascular Disease and Undertreatmenmentioning
confidence: 99%